The Development and management of school guidance programs - Gibson, Robert L.; Mitchell, Marianne H. ;Higgins, Robert E. (Dubuque : W.C. Brown Co. Publisher, 1973)
The effectiveness of school guidance programs is determined in large measure by three factors: (1) accurate needs assessments; (2) appropriate planning to serve the identified need; and (3) effective program leadership and management. With these factors in mind, this book has been designed to give the reader an introduction to guidance program development, management and leadership.
1. Introduction -- 2. The Personnel for guidance -- 3. Initiating and developing school guidance programs -- 4. Program leadership and management -- 5. The elementary school guidance program -- 6. The Secondary school guidance program -- 7. The Guidance and student personnel program in the junior community college -- 8. Evaluation and change.
Includes index.
Keywords: COUNSELING